2002
DOI: 10.1258/095646202760326471
|View full text |Cite
|
Sign up to set email alerts
|

Alternative therapy use in HIV-infected patients receiving highly active antiretroviral therapy

Abstract: The extent of use of alternative therapies, psychosocial and disease-specific variables predictive of alternative therapy use, and factors motivating the use of alternative therapies in HIV-infected patients receiving highly active antiretroviral therapy (HAART) have not been well defined. Types of alternative therapies used, demographic and medical data, coping (Billing and Moos inventory of coping with illness styles), social support (Irwing and Sarason questionnaire), sense of personal control (Pearlin's Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0
7

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 22 publications
1
20
0
7
Order By: Relevance
“…ore than half of HIV-infected patients express interest in taking some kind of complementary therapy in addition to their antiretroviral regimens at some point during the course of treatment (15,16,19). These patients usually choose dietary and herbal supplements and take them without medical supervision.…”
mentioning
confidence: 99%
“…ore than half of HIV-infected patients express interest in taking some kind of complementary therapy in addition to their antiretroviral regimens at some point during the course of treatment (15,16,19). These patients usually choose dietary and herbal supplements and take them without medical supervision.…”
mentioning
confidence: 99%
“…Thirty-eight percent of respondents used alternative therapies in a survey of 118 HIV-infected patients receiving highly active antiretroviral therapy. Of particular concern is that physicians were unaware of the patients' alternative therapy use in 67% of herbal therapy users and 100% of dietary supplement users [46]. In light of several recent investigations that showed that complementary alternative medicine significantly altered antiretroviral blood concentrations, many investigators have turned their attention to the combination of herbal remedies and antiretroviral medications.…”
Section: Complementary Alternative Medicinementioning
confidence: 99%
“…El uso de TAC parece ser comú n en los pacientes infectados por el virus de la inmunodeficiencia humana (VIH), sin que haya disminuido a pesar de la actual disponibilidad de los llamados esquemas de tratamiento antirretroviral de gran actividad (TARGA) [5][6][7][8][9][10][11][12][13][14][15] . No obstante, la prevalencia del uso de TAC varía notablemente entre los diferentes estudios publicados en la literatura mé dica [5][6][7][8][9][10][11][12][13][14][15] , probablemente debido a diferencias sociodemográ ficas entre las poblaciones estudiadas, que hacen que los resultados obtenidos en una població n no sean extrapolables al resto.…”
Section: Introducció Nunclassified
“…No obstante, la prevalencia del uso de TAC varía notablemente entre los diferentes estudios publicados en la literatura mé dica [5][6][7][8][9][10][11][12][13][14][15] , probablemente debido a diferencias sociodemográ ficas entre las poblaciones estudiadas, que hacen que los resultados obtenidos en una població n no sean extrapolables al resto. Por este motivo, conocer la prevalencia del consumo de TAC y de los factores relacionados con el mismo en una població n específica es de gran interé s para los mé dicos clínicos, sobre todo cuando se refiere a sustancias con riesgo potencial de poner en peligro de la salud de los pacientes, como las plantas medicinales.…”
Section: Introducció Nunclassified
See 1 more Smart Citation